The Influence of Brand Satisfaction on Brand Loyalty with Emotional Brand Attachment and Brand Love as Intervening Variables on Millennial Consumer at Clinic Ms Glow Medan - Fauziah Fauziah; Endang Sulistia Rini; Syafrizal Helmi Situmorang (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to test the influence of Brand Satisfaction on Brands Loyalty with Emotional Brand Attachment and Brand Love as Intervening Variables. In this study, the population was Millennial Consumers at Clinic Ms Glow Medan. Sample used in this research were 150 respondents, sampling technique using purposive sampling. Data collection uses questionnaires and answers assessed using a Likert scale. Data analysis uses SmartPLS with analysis methods SEM (Structural Equation Modeling). The results of this research show that brand satisfaction, emotional brand attachment, and brand love have a positive and significant effect on brand loyalty. Brand satisfaction has a positive and significant effect on emotional brand attachment. Brand satisfaction has a positive and significant effect on brand love. Emotional brands attachment has a positive and significant effect on brand love. Brand satisfaction has a positive and significant effect on brand loyalty on Millennial Consumers at Clinic Ms Glow Medan mediated by emotional brand attachment. Brand satisfaction has a positive effect and significant impact on brand loyalty on Millennial Consumer at Clinic Ms Glow Medan which is mediated by brand love, in this case it is in the form of complementary mediation.